UMPSA Singgah Sahur celebrates orphans and security agencies - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
KAJANG, 28 March 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) celebrated and delivered donations of necessities and duit raya to 55 orphans, poor and asnaf aged 1 to 6 years old at Pertubuhan Warisan Suci in Kajang.